Efficiency and Competition in the Malaysian Banking Market: Foreign versus Domestic Banks - Rossazana, Ab. Rahim (Gadjah Mada University, 2017)
The aim of this paper is to investigate how efficient the performance of the Malaysian banking market is, using a data envelopment analysis approach, in the context of the increasing presence of foreign banks. Specifically, two measures of efficiency are constructed, cost and profit efficiency, by utilizing bank-level data from Malaysian commercial banks, over the period from 2003 to 2014. The results obtained show the domestic banks are more efficient than their foreign banking counterparts for both measures of efficiency. Next, the Lerner index approach was employed to measure competition and finally, Granger causality tests were undertaken to answer the question, does competition foster efficiency? The results of the causality tests support a positive effect of competition on the cost and profit efficiency of Malaysian banks. With regard to the financial liberalization, the findings imply that higher competitive pressure may offset the market power of individual banks; however, eventually it will result in efficiency gains for the Malaysian banks